Axisymmetric thin film flow on a flat disk foil subject to intense radial electric fields - Wang, Z.; Zhang, C.; Xia, H.; Xie, Q.; Deng, W. (Physics of fluids (1994), 2022)
The presence of intense radial electric fields on a wetted disk foil of fingernail size results in the formation of a large number (up to ∼1000) of cone-jets and electrosprays (Wang et al., “Massively multiplexed electrohydrodynamic tip streaming from a thin disc,” Phys. Rev. Lett., 126, 064502, 2021). This massively multiplexed electrohydrodynamic tip streaming phenomenon offers a simple and convenient way of creating quasi-monodisperse droplets at high throughput. The structure of the axisymmetric liquid film flow on the disk determines the number and distribution of the cone-jets. In this work, we quantitively study the flow of the axisymmetric thin liquid film subjected to a radial electric field. The liquid film profile is found to be concave with a circular ridge, at which multiple Taylor cones are anchored. The liquid film thickness is experimentally quantified with a fluorescence imaging method, and the results are in decent agreement with the film profile model based on the lubrication theory. The velocity field in the liquid film was experimentally obtained by particle tracking velocimetry (PTV). The results shed light on the understanding of the multiplexed electrohydrodynamic tip streaming from a thin disk.